2021
DOI: 10.1177/2473974x211032644
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Online Materials Related to Vocal Cord Leukoplakia

Abstract: Objectives To assess readability and understandability of online materials for vocal cord leukoplakia. Study Design Review of online materials. Setting Academic medical center. Methods A Google search of “vocal cord leukoplakia” was performed, and the first 50 websites were considered for analysis. Readability was measured by the Flesch Reading Ease Score (FRES), Flesch-Kincaid Grade Level (FKGL), and Simple Measure of Gobbledygook (SMOG). Understandability and actionability were assessed by 2 independent revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…This score is at the lower end of the range of scores for other topics within otolaryngology that report scores between 66% and 74%. [4][5][6] Moreover, the actionability score in this study, 40.55% 6 23.86%, was poor and similar to scores reported in some studies, 35 although several studies in otolaryngology have reported lower actionability scores between 10% and 20%. 5,36 This difference might be due in part to the relatively large patient population SLPs and laryngologists care for, ranging from professional singers, patients with cancer, patients with Parkinson's disease, and TGD patients.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This score is at the lower end of the range of scores for other topics within otolaryngology that report scores between 66% and 74%. [4][5][6] Moreover, the actionability score in this study, 40.55% 6 23.86%, was poor and similar to scores reported in some studies, 35 although several studies in otolaryngology have reported lower actionability scores between 10% and 20%. 5,36 This difference might be due in part to the relatively large patient population SLPs and laryngologists care for, ranging from professional singers, patients with cancer, patients with Parkinson's disease, and TGD patients.…”
Section: Discussionsupporting
confidence: 84%
“…[4][5][6] Moreover, the actionability score in this study, 40.55% 6 23.86%, was poor and similar to scores reported in some studies, 35 although several studies in otolaryngology have reported lower actionability scores between 10% and 20%. 5,36 This difference might be due in part to the relatively large patient population SLPs and laryngologists care for, ranging from professional singers, patients with cancer, patients with Parkinson's disease, and TGD patients. These myriad indications for voice care, often listed all together on provider websites, require clear organization and actionable items to differentiate types of care, leading to inherently higher actionability scores.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Even when health apps contain evidence‐based and comprehensive health information, they remain ineffective when they do not provide accessible and inclusive content. The medical informatics literature has an increasing number of publications on the importance of making digital material accessible and usable by diverse users 15,16,29–37 . Inclusivity considerations also include image representation of diverse populations, content availability in languages other than English, and accommodations for those with disabilities, such as hearing or voice impairments.…”
Section: Introductionmentioning
confidence: 99%